Do Fans Care About Compliance to Doping Regulations in Sports? The Impact of PED Suspension in Baseball. (May 2017) - Cisyk, Jeffrey; Courty, Pascal
There is little evidence in support of the main economic rationale for regulating athletic doping that doping reduces fan interest. The introduction of random testing for performance-enhancing drugs (PEDs) by Major League Baseball (MLB) offers unique data to investigate the issue. The announcement of a PED violation (a) initially reduces home-game attendance by 8%, (b) has no impact on home-game attendance after 15 days, and (c) has a small negative impact on the game attendance for other MLB teams. This is the first systematic evidence that doping decreases consumer demand for sporting events.